An energy consumption study for a Malaysian University - Tang, Fu Ee (World Academy of Science, Engineering and Technology, 2012)
The increase in energy demand has raised concerns over adverse impacts on the environment from energy generation. It is important to understand the status of energy consumption for institutions such as Curtin Sarawak to ensure the sustainability of energy usage, and also to reduce its costs. In this study, a preliminary audit framework was developed and was conducted around the Malaysian campus to obtain information such as the number and specifications of electrical appliances, built-up area and ambient temperature to understand the relationship of these factors with energy consumption. It was found that the number and types of electrical appliances, population and activities in the campus impacted the energy consumption of Curtin Sarawak directly. However, the built-up area and ambient temperature showed no clear correlation with energy consumption. An investigation of the diurnal and seasonal energy consumption of the campus was also carried out. From the data, recommendations were made to improve the energy efficiency of the campus.